Regime change in Malaysia GE14 and the end of UMNO-BN's 60-year rule - Loh, Francis Kok-Wah 1951-; Netto, Anil (Strategic Information and Research Development Centre Aliran Kesedaran Negara (ALIRAN), 2018)
This book is a collection of 40-plus essays by 30-plus Malaysians about GE14 on 9 May 2018. It is a record of an unprecedented defeat of the UMNO-BN government, in power since 1957, and its replacement by Pakatan Harapan, a newly formed coalition. These essays discuss the major election issues, the principal actors, the campaign, the results and where we might be headed in the next decade. . Regardless of the specifics, GE14 has ushered in Regime Change. We are witnessing change that goes beyond the displacement of one government by another as occurs when a different party takes over in western liberal democracies. Regime Change is more than that in at least three aspects: first, there are changes in the make-up of the socio-economic alliance that is backing up the new government; second, we see changes in the major political institutions, as in the whittling down of the humongous Prime Minister's Department and impending reform of some others like the MACC, the SPR and the civil service, and the replacement of self-serving, inefficient top personnel; and third, the adoption of new policies in public transport, education, labour and welfare concerns or disaster management - which are hopefully more pro-people and less wasteful of resources compared to previous policies.